PENEGAKAN HUKUM SATUAN TUGAS LALU LINTAS (SATLANTAS) KEPOLISIAN DALAM MENANGANI TINDAK PIDANA PELANGGARAN LALU LINTAS OLEH MASSA AKSI UNJUK RASA DI KOTA PEKANBARU - PANUSUNAN SIREGAR; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the rights of Indonesian citizens is to express opinions in public aswritten in Article 28 E Paragraph 3 of the 1945 Constitution of the Republic ofIndonesia. The purpose of writing this thesis, namely: First, to determine the lawenforcement of the Traffic Police in handling traffic violations by mass demonstrations in Pekanbaru City. Second, to find out the inhibiting factors for the Traffic Police of the Police in handling traffic violations by mass demonstrations in Pekanbaru City. Third, to find out the efforts of the Traffic Police of the Police to enforce the law against criminal acts of traffic violations byprotesters in Pekanbaru City.This research is sociological. Data sources are primary data andsecondary data consisting of primary legal materials, secondary legal materialsand tertiary legal materials. Data collection techniques in this study wereinterviews, questionnaires and literature study and data analysis using qualitativeanalysis with deductive methods.From the research results, there are three main conclusions. First, the lawenforcement of the Traffic Police of the Police in dealing with criminal acts oftraffic violations by mass demonstrations in Pekanbaru City clearly regulates therules of law regarding traffic violations committed by demonstration masses. Inthe implementation, there was still no evidence of any action. Second, theinhibiting factor for the enforcement of the Police Traffic Police in dealing withcriminal acts of traffic violations by mass demonstrations in Pekanbaru City isthat the quantity of the Police is not balanced with the mass of demonstrations,prioritizes consideration, lack of awareness, regulations have not provided legalcertainty. Third, the efforts of the Police Traffic Police in enforcing the lawagainst traffic violations by mass demonstrations in Pekanbaru City need to payattention to the applicable legal rules. Author's suggestion, First, enforcement ofthe traffic police in dealing with criminal acts of traffic violations by massdemonstrations in the city of Pekanbaru is enforcement of traffic violations is anattitude in upholding the law. Second, the inhibiting factors for law enforcementof the Traffic Police of the Police in dealing with criminal acts of traffic violationsby mass demonstrations in Pekanbaru City need to know the inhibiting factors oflaw enforcement. Third, the efforts of the Traffic Police Unit in enforcing the lawagainst traffic violations by mass demonstrations in Pekanbaru City are toimprove the education of the traffic community, an alternative effort. it isnecessary to increase the quality and quantity of police personnel and strengthenlegal certainty in writing and unwritten / application.Keywords: Mass Action - Offense – Traffic